Translocated Species Exceed Alien Species in Homogenizing Freshwater Fish Assemblages - Jie Wang; Juan Tao; Sébastien Brosse; Chunlong Liu; Qiyue Chen; Guangjie Cheng; Jianshuang Tao; Chengzhi Ding (Global Change Biology, 2025)
Human‐driven introductions of nonnative species are accelerating biotic homogenization, threatening the distinctiveness of biota worldwide. However, the patterns and drivers of homogenization caused by nonnatives originating from other ecoregions (alien species) and those originating from the same ecoregion as natives (translocated species) remain highly uncertain across taxonomic, phylogenetic, and functional biodiversity dimensions. This study compared the contributions of alien versus translocated fishes to the homogenization of freshwater fish assemblages, as well as the underlying drivers, in a biodiversity hotspot (Yunnan, China). We first quantified the cumulative beta‐diversity changes caused by alien and translocated species across biodiversity dimensions prior to 1960 (P1960), 1980 (P1980), 2000 (P2000), and 2022 (P2022), respectively. We then assessed the influence of anthropogenic disturbance intensity, habitat variability, and the biotic resistance of native fauna on beta‐diversity changes. We found an asynchronous pattern of homogenization and differentiation caused by alien and translocated fishes. Alien fishes initially contributed to differentiation, which then shifted to homogenization over time in the taxonomic and functional dimensions, whereas phylogenetic differentiation remained consistent through time. In contrast, translocated fishes consistently drove homogenization across all biodiversity dimensions over time. The cumulative intensity of homogenization caused by translocated fishes was up to four times greater than that induced by alien fishes. Anthropogenic disturbance intensity and habitat variability, along with native biotic resistance, positively contributed to fish assemblage homogenization through both direct and indirect pathways. Our findings reveal that translocated species have caused more pronounced homogenization effects in freshwater fish assemblages. Conservation and management strategies should prioritize the prevention of intra‐regional species translocations and the mitigation of anthropogenic disturbances to preserve ecological distinctiveness and integrity.